A Study of Serials use at Kwame Nkrumah University of Science and Technology Library, Kumasi - Lawoe, M.A. (Ghana Library Journal, 2006)
This study was undertaken to find out how intensively the serials collection of the Kwame Nkrumah University of Science and Technology (KNUST) Library was being used by students and Faculty and to establish how adequate the collection was to their subject needs. The principal users of the KNUST Library are the students, both undergraduate and post-graduate, lecturers and research fellows of the University. A sample population of 483 registered users of the Library, constituting one-tenth of total registered users were selected. The 483 spanned all the various categories of users and these were served with questionnaires. A high return rate of 82.6% was attained. It was clear from the results of the study that the serials collection was being fairly used. It could however, not be firmly established whether the collection was adequate to the subject needs of all the clientele. The undergraduate student users were identified as one group that significantly used journals and this was because lecturers were recommending the journals to them. The study, unearthed some loopholes and lapses in the collection and its management, which needed to be addressed in order to satisfy, adequately, patrons of the Library. Thus, recommendations made, included engaging in new and intensive methods of user education in the use of serials; and an intensive current awareness and the provision of SDI services.